Einkommens- und Vermögensverteilung: zu ungleich? - Stefan Bach; Hermann Adam; Judith Niehues; Christoph Schröder; Christian Frey; Christoph A. Schaltegger; Norbert Berthold; Klaus Gründler (Wirtschaftsdienst, 2014)
Die Einkommens- und Vermögensverteilung hatte sich in Deutschland vor dem Beginn der Finanzkrise zunehmend ungleich entwickelt, seitdem aber ist die Ungleichheit zurückgegangen. Ob Ökonomen beurteilen können und sollen, was eine "richtige und gerechte" Einkommensverteilung ist, bleibt fraglich. Zusammenhänge können allerdings diskutiert werden: Ist Ungleichheit der Preis des Wachstums? Wie ist die Situation in Deutschland im internationalen Vergleich einzuschätzen? Können Einkommen durch soziale Mobilität egalitärer verteilt werden? – – The distribution of income and wealth in Germany grew increasingly unequal until the beginning of the fi nancial crisis. But inequality has not risen in either Germany or Switzerland since 2005. Nevertheless, Germans overestimate inequality . The German gap between reality and perception of inequality is important to investigate, as the subjective assessment of inequality infl uences redistribution preferences. Rising inequality may damage social stability and democracy, but it is unclear whether economists are able to assess a 'proper and just' distribution. Interdependencies are discussed: Does a more equal distribution create negative effects on economic growth? How does Germany rank internationally with regard to distribution? Social mobility rates differ substantially across countries; what are the implications for economic policy?
Keywords: 330; Einkommensverteilung; Vermögensverteilung; Soziale Ungleichheit; Soziale Mobilität; Soziale Gerechtigkeit; Umverteilung; Öffentliche Meinung; Deutschland; Schweiz